NITROGEN, WATER AND BENZENE ADSORPTION IN MESOPOROUS CARBON (CMK-1) AND COMMERCIAL ACTIVATED CARBON (NORIT SX22) - Paulina Taba (Indonesian Journal of Chemistry, 2009)
Adsorption at various interfaces has attracted the attention of many scientists. This article discusses gas-solid and vapour-solid adsorption in CMK-1 and Norit SX22 using nitrogen, water and benzene as adsorbates. For comparison, MCM-48 used as template in synthesizing CMK-1 was also utilized as adsorbent. Results showed that the shape of nitrogen isotherm for CMK-1 is categorized as Type IV shape, whereas activated carbon (Norit SX2) has Type I shape with a hysteresis loop at P/P0 > 0.5, which is a H4 type of hysteresis. The shape of nitrogen isotherm for MCM-48 is categorized as Type IV shape with small hysteresis loop observed at P/P0 above 0.45, indicating that the larger pores are filled at high P/P0, which is typical of an H3 hysteresis loop The amount of nitrogen adsorbed in activated carbon at the high relative pressure is considerably smaller than that in CMK-1. The hydrophobicity feature of CMK-1 is the same as activated carbon (Norit SX2), but slightly different to the template MCM-48. The affinity of CMK-1 to benzene is considerably higher than activated carbon, suggesting the promising future of CMK-1 to be used as a selective adsorbent for the removal of organic compounds from water environment.